2006
DOI: 10.1073/pnas.0509685103
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of butterfly mate preference and wing color preference cue at the genomic location ofwingless

Abstract: Sexual isolation is a critical form of reproductive isolation in the early stages of animal speciation, yet little is known about the genetic basis of divergent mate preferences and preference cues in young species. Heliconius butterflies, well known for their diversity of wing color patterns, mate assortatively as a result of divergence in male preference for wing patterns. Here we show that the specific cue used by Heliconius cydno and Heliconius pachinus males to recognize conspecific females is the color o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
363
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 330 publications
(381 citation statements)
references
References 50 publications
12
363
2
4
Order By: Relevance
“…These expression differences could be caused by cis-regulatory changes in the genes examined or by changes in their transcriptional activators. Although specific genetic changes have not yet been identified, studies mapping the genetic basis of variable wing pigmentation are consistent with changes at pleiotropic regulatory genes: Distal-less is associated with quantitative variation in eyespot size in Bicyclus anynana [31], wingless is associated with wing color in hybrids of Heliconius species [32], and engrailed/invected is associated with wing pattern polymorphism in Papilio dardanus [33]. Increased mapping resolution and/or functional analyses are ultimately needed to separate the effects of these candidate genes from linked loci.…”
Section: Beyond Drosophilamentioning
confidence: 92%
See 1 more Smart Citation
“…These expression differences could be caused by cis-regulatory changes in the genes examined or by changes in their transcriptional activators. Although specific genetic changes have not yet been identified, studies mapping the genetic basis of variable wing pigmentation are consistent with changes at pleiotropic regulatory genes: Distal-less is associated with quantitative variation in eyespot size in Bicyclus anynana [31], wingless is associated with wing color in hybrids of Heliconius species [32], and engrailed/invected is associated with wing pattern polymorphism in Papilio dardanus [33]. Increased mapping resolution and/or functional analyses are ultimately needed to separate the effects of these candidate genes from linked loci.…”
Section: Beyond Drosophilamentioning
confidence: 92%
“…An association with pigmentation has been described for diverse behaviors, including swarming [48], feeding [49], social dominance [50], mate preference [32], and courtship display [51]. The molecular basis for these associations, as well as the data supporting them, are also varied.…”
Section: Pigmentation and Behaviormentioning
confidence: 99%
“…That is, geographical races of H. melpomene behave as a single biological species, as do geographical races of H. cydno and H. timareta , respectively. Heliconius pachinus appears to be intrinsically isolated from H. cydno, as implied previously (Kronforst, Young, & Gilbert, 2007; Kronforst et al., 2006). In contrast, H. heurippa is only isolated from H. cydno by allopatry, suggesting that these two forms are parts of a single biological species (Brower, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Heliconius butterflies have likewise become a model system for studying patterns of speciation in the putative presence of ongoing gene flow (Dasmahapatra et al., 2012; Kronforst et al., 2006, 2013; Nadeau et al., 2013). Most Heliconius species are Müllerian mimics of one another, as well as other unpalatable taxa, displaying shared, aposematic wing patterns that are maintained by positive numerically dependent selection.…”
Section: Introductionmentioning
confidence: 99%
“…Such comparative studies have revealed the evolutionary flexibility of developmental mechanisms at the species level (e.g. Raff et al, 1999;Kopp et al, 2000;Gompel and Carroll, 2003;Hoekstra and Nachman, 2003;Voss and Smith, 2005;Kronforst et al, 2006;Protas et al, 2006), allowing insights into the evolution of novel phenotypes (e.g. Wittkopp et al, 2002) as well as the conservation of ontogenetic functions (e.g.…”
Section: Introductionmentioning
confidence: 99%